Dietary diversity predicts the adequacy of micronutrient intake in 6- to 23-month-old children regardless of the season in rural Southern Benin - Amoussa Hounkpatin, Waliou; Koukou, Elie; Termote, Céline; Ntandou, Gervais; Mitchodigni, Irene; Bodjrenou, Sam; Alaofe, Halima (SAGE Publications, 2023)
Background: The Infants and Young Children Dietary Diversity Score (IYC-DDS-7) has been validated to assess dietary quality in children. However, its applicability to predict the adequacy of micronutrient intake remains a challenge in all contexts. Design and Methods: A 24-hour dietary recall assessment was conducted on a sample of 628 children aged 6 to 23 months in the plenty season (PS) as well as in the lean season (LS). The IYC-DDS-7 was calculated based on 7 food groups, whereas the mean micronutrient density adequacy (MMDA) for 11 micronutrients. The β regression models were used to assess the relationship between IYC-DDS and MMDA and differences in nutrient intake between the 2 seasons. A receiver-operating characteristic curve analysis was also performed to determine IYC-DDS-7 cutoff levels that maximized sensitivity and specificity in assessing dietary quality and predicting MMDA below- or above-selected cutoff levels. Results: Participating children’s MMDA was 56.9% ± 12.8% versus 61.9% ± 8.6% and IYC-DDS-7 was 3.43 ± 1.5 versus 3.77 ± 1.0 in the PS and LS. The IYC-DDS-7 had a positive correlation with MMDA, irrespective of the season. For a 1-unit increase in IYC-DDS-7, MMDA increased by a mean of 10.7% (CI, 8.3%-13.1%; P < .001). The minimum threshold of the 4 food groups corresponded to a sensitivity of 76% and 61% and a specificity of 75% and 70% for the prediction of inadequate diet in the PS and LS, respectively. Conclusions: The IYC-DDS-7 predicted MMDA, regardless of seasons for infants and young children. The IYC-DDS-7 cutoff of 4 groups performed well in classifying children with low-diet quality.